Customer satisfaction towards bus express services in Kota Bharu Kelantan - Nabil Fikri Mohamad (2012)
The research is about to know the customers satisfaction towards bus express service in Kota Bharu. A sample of 100 respondents that using bus express in Kota Bharu to answer the questionnaire, which asked whether the chosen factors such as reliability, responsiveness, tangibles, assurance and empathy that influence the customers satisfaction in using bus express. In this study, the researcher apply the reliability test to know the variables are significant or not and use the correlation analysis to analyses the data. Correlations are applied in this study because researcher wants to know the related preferences from the factors such as reliability, responsiveness, tangibles, assurance and empathy to the customer satisfaction in using bus express. The results, most of the bus express users in Kota Bharu was agreed and satisfied with the factors in this study but bus express company that provide the service still have to upgrade in a certain part in their services such as timeliness and ticket price.